Carotid artery imaging for secondary stroke prevention: both imaging modality and rapid access to imaging are important. - Wardlaw, J; Stevenson, MD; Chappell, F; Rothwell, P; Gillard, J; Young, G; Thomas, S; Roditi, G; Gough, M (2009)
BACKGROUND AND PURPOSE: Patients with transient ischemic attack require carotid imaging to diagnose carotid stenosis. The differing sensitivity/specificity and availability of carotid imaging methods have created uncertainty over which noninvasive method is best and whether intra-arterial angiography is still required. We evaluated the influence of carotid imaging methods on secondary stroke prevention. METHODS: We modeled the effect of different carotid imaging strategies and timing on endarterectomy workload, stroke, and death at 1 and 5 years. We used all available data on stroke prevention after transient ischemic attack from systematic reviews (carotid imaging, medical and surgical interventions), population-based transient ischemic attack/stroke studies, government statistics, and stroke prevention clinics. RESULTS: Choice of imaging strategy affected speed of assessment, strokes prevented, and endarterectomy workload. The number of strokes prevented at 5 years varied by up to 22 per 1000 patients between imaging strategies for a given time to assessment. Delaying endarterectomy from 14 to approximately 30 days would fail to prevent up to 11 strokes per 1000 patients depending on the imaging strategy. Sensitive fast imaging (eg, ultrasound) was best for patients seen early; specific imaging (eg, CT angiography or contrast-enhanced MR angiography) was best for patients seen late after transient ischemic attack. Intra-arterial angiography conferred no advantage over noninvasive imaging. CONCLUSIONS: Rapid access to sensitive noninvasive carotid imaging prevents most strokes. However, imaging strategies differ in their effect on stroke prevention by as much as 22 per 1000 patients and optimal imaging varies with time after transient ischemic attack TIA. Routine intra-arterial angiography should be avoided.